Analisis Persepsi Konsumen Bisnis Sesudah Pemboikotan Produk Unilever Di Kecamatan Sitiung - Larisa, Lioni Septi Apanda; Gusteti, Yesi; Purwanto, Kelik; Resty, Fenisi (Cattleya Darmaya Fortuna, 2024)
On the boycott of product examples that had an impact on at that time Life Boy liquid soap at Warung Amoy, Pepsodent and sunlight dish soap at the Iqbal stall, during the boycott of the amoy stall experienced the impact of the boycott for 3 months and the Iqbal stall for 3- This study is to review and analyze the Analysis of Consumer Perception Before and After the Boycott of Unilever Products in Sitiung District. This type of research is qualitative by taking data in the form of interviews, this research was conducted in Kekematan Sitiung using 5 informants who owned wholesale stalls, when the boycott occurred from 5 stalls only 2 stalls had an impact 5 months. During the boycott, there were 2 stores impacted, but only briefly within a period of 2 weeks, and 1 store had no impact at all with the news of the boycott of unilever products. As long as there is news of a boycott, there is indeed an effect in several places and there is no influence at all about the boycott of unilever products.